Optimal Walking Speed Transitions for Fully Actuated Bipedal Robots - Murali, Vishal; Ames, Aaron D.; Verriest, Erik I. (Proceedings of the IEEE Conference on Decision & Control, 2019)
In this paper, we utilize the Partial Hybrid Zero Dynamics (PHZD) framework to find a continuous family of stable periodic orbits on the PHZD surface. We find optimal controllers to transition between these types of orbits subject to PHZD constraints, along with finding optimal periodic orbits associated to different PHZD surfaces for different walking speeds. Additionally, optimal controllers that form a connecting surface between these distinct PHZD surfaces, along with transitions between them are synthesized. The two methods are compared with performance metrics associated with the cost of transport. The results are illustrated on a 5 degree of freedom planar bipedal robot.